Three essays on financial risk - Yao, Kai (2019)
The thesis contributes to the literature on behavioural finance and price jumps by moving beyond the traditional framework of the efficient market hypothesis. The aim of the thesis is to deepen the understanding of actual financial markets rather than the ideal world described by that hypothesis. This thesis empirically investigates three related topics: managerial traits; the incentives for risk-taking provided by managerial compensation packages; and price jumps.